Revisiting English As A Global Language - Silfia Asningtias (Department of English Language Education, UIN Sunan Ampel Surabaya, 2017)
As English has become a powerful tool to ‘conquer’ the world, the needs to consider the issues arise English as an International language has become paramount. The arguments of who ‘own’ English sparks other related matters, such as the native speaker and non-native speakers as well as native speakers. In addition, it also standard and nonstandard English, that come up as the varieties of English blooming is unstoppable. On Norton’s statement of the issues of English in a global world provoke debate on whether the aforementioned is for better or for worse. This essay analyzes the perspective of experts in the dichotomy globally, meanwhile seeking the enlightenment of the situation in Indonesia locally. The discussion leads to awareness that English and the learner’s agency. As the needs of English in the global era is indispensable, English would be for better than for worse.